2022
DOI: 10.48550/arxiv.2201.09879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak deflection angle of Kazakov-Solodukhin black hole in plasma medium using Gauss-Bonnet theorem and its greybody bonding

Wajiha Javed,
Iqra Hussain,
Ali Övgün

Abstract: In this paper, we study light rays in a Kazakov-Solodukhin black hole. To this end, we use the optical geometry of the Kazakov-Solodukhin black hole within the Gauss-bonnet theorem. We first show the effect of the deformation parameter a on the Gaussian optical curvature, and then we use the modern method popularized by Gibbons and Werner to calculate the weak deflection angle of light. Our calculations of deflection angle show how gravitational lensing is affected by the deformation parameter a. Moreover, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Sanchez showed that the absorption spectrum as a function of the frequency makes clear oscillations characteristic of a diffraction pattern, where the oscillations occur around the constant value of the geometrical optics with decreasing amplitude and constant period. The absorption cross-section for black holes has been studied in the literature for various black hole spacetimes [46,108,[135][136][137][138][139][140][141][142][143][144][145][146], especially for the low-frequency behaviour of the absorption and for the zero-frequency limit (it becomes equal to the surface area of the black hole horizon) [136,147,148], as well as the high-frequency behaviour of the scalar absorption via Sinc approximation [134,149,150].…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez showed that the absorption spectrum as a function of the frequency makes clear oscillations characteristic of a diffraction pattern, where the oscillations occur around the constant value of the geometrical optics with decreasing amplitude and constant period. The absorption cross-section for black holes has been studied in the literature for various black hole spacetimes [46,108,[135][136][137][138][139][140][141][142][143][144][145][146], especially for the low-frequency behaviour of the absorption and for the zero-frequency limit (it becomes equal to the surface area of the black hole horizon) [136,147,148], as well as the high-frequency behaviour of the scalar absorption via Sinc approximation [134,149,150].…”
Section: Introductionmentioning
confidence: 99%
“…This deflection angle differs significantly from the vacuum case. Several authors have studied the impact of different plasma topologies and works on light propagation, providing deep insight into this fascinating area of research [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Understanding gravitational lensing in plasma has significant implications for our understanding of the universe and the behavior of light in different environments.…”
Section: Introductionmentioning
confidence: 99%